Politeness Maxims Used by English Students Program Study at STKIP Tama Siswa Bima - Annisah, Annisah; Waliyudin, Waliyudin; Ramli, Ramli; Nurbaya, Nurbaya (Jurnal Ilmiah Mandala Education (JIME), 2021)
The aims of this research are to find out the types and the function of most dominant types of politeness maxim used by students in classroom interaction during learning process. The subject of this research is the students of English Program Study, the STKIP Taman Siswa Bima. This research used descriptive-qualitative method. Samples on this research consist of 25 students. To collect the data video recorded was used to record the students’ utterance and interaction in the class. The students’ utterances transcribed and analyze based on types and function of most dominant type’s politeness maxim. The result of this research there were six types of politeness maxim applied in classroom interaction, they were Tact Maxims, Generosity Maxim, Approbation maxim, Agreement Maxim, Sympathy Maxim, Modesty Maxim. The dominant types were used by students is tact maxim, and it plays several functions such as declarative function, interrogative function, imperative function, the apology function